AVALIAÇÃO ANTITUMORAL IN VITRO E IN VIVO DE NANOPARTÍCULAS DE PCL CONTENDO RESVERATROL EM MODELO DE MELANOMA MURINO - Carletto, Bruna (2015)
Melanoma is a very lethal skin tumor and, when widespread, presents unfavorable prognosis. Therefore, new drugs and treatments are important to the search for more promising results. Treatment of this type of tumor surgery necessarily depend on having little effect on the supplementary chemotherapy. Studies have shown resveratrol as a drug that acts in different stages of carcinogenesis. Allied to this, modified release systems of drugs are being studied to improve unwanted features and optimize their actions. The aim of this study was to develop polymeric nanocapsules containing resveratrol and assess their potential antitumor in B16F10 melanoma strain. The nanocapsules of poly -caprolactone) (PCL) containing resveratrol were successfully prepared by interfacial deposition of preformedpolymer. All formulations showed encapsulation efficiency values suitable above 97%. Nanocapsules revealed spherical shape with smooth surface. Infrared Fourier transform spectra indicated no chemical interaction between the polymer and resveratrol after the nanoencapsulation. The analysis of X-ray diffraction showed that the process of nanoencapsulation led to an amorphisation of the system. Cell viability assays for neutral red and MTT confirmed that resveratrol-containing nanocapsules have cytotoxic effect on murine melanoma cells at concentrations of 300 and 100 micrometers. When analyzed the morphology of the cells treated with resveratrol free, it can be seen that they enter into the process of cell death by apoptosis. In the in vivo assay, the results demonstrated that treatment with resveratrol-containing nanocapsules led to a reduction in tumor volume of the mice in the groups treated with resveratrol and free controls. Treated animals also showed an increase in body mass suggesting that these animals had a better response to treatment compared to the control group. Histological analysis revealed an increase in necrotic area in the tumor and inflammation in the animals treated with the nanocapsules containing resveratrol and the treatment also led to the development of non-pulmonary hemorrhage and metastasis. These results indicate that the nanocapsules prepared from the PCL containing resveratrol have antiproliferative action front melanoma cells, with an interesting alternative in their treatment.